Inuvialuit Use of the Beaufort Sea and its Resources, 1960-2000 - Usher, Peter J. (ARCTIC, 2002)
Comprehensive, census-type surveys of Inuvialuit harvesters were conducted in the Inuvialuit Settlement Region (ISR) in the 1960s (Area Economic Surveys) and 1970s (Inuit Land Use and Occupancy Project) and in the 1990s (Inuvialuit Harvest Study). These surveys, supplemented by other case studies, provide a basis for comparing Inuvialuit use of the Beaufort Sea and its resources in the 1960s and the 1990s. The geographic extent of harvesting was about the same in both decades. The number of harvesters grew, although by less than the rate of population growth. Mean annual harvest of country food per hunter declined from 2083 kg/yr to 707 kg/yr. The chief reason for the decline in harvest was the near-abandonment of dogs for transport. If we take into account the share of country food likely consumed by dogs, the per capita harvest of country food for human consumption may not have changed significantly between the two decades. What has changed, however, is the composition of the harvest: the ratio (by weight) of country foods from marine and terrestrial sources was 75:25 in the 1960s, but 45:55 in the 1990s. Available country food amounted to 115.2 kg/capita/yr in the 1990s, a significant contribution to the household economy. Thus, contrary to many predictions in the 1960s, subsistence harvesting persists as a significant economic as well as cultural preoccupation in the lives of Inuvialuit today. The results of this study suggest that the measurement of subsistence and commercial harvesting in terms of location, participation, inputs, and outputs is of continuing importance for fish and wildlife management and for economic planning. Des enquêtes par recensement détaillées portant sur les exploitants pêcheurs ont été menées dans la Région désignée des Inuvialuit (RDI) au cours des années 1960 (Enquêtes économiques dans le secteur), des années 1970 (Projet d'utilisation et d'occupation du territoire par les Inuits) et des années 1990 (Étude sur les prélèvements par les Inuvialuit). Ces enquêtes, complétées par ...